2015
DOI: 10.3389/fpsyg.2015.01499
|View full text |Cite
|
Sign up to set email alerts
|

Flow theory – goal orientation theory: positive experience is related to athlete’s goal orientation

Abstract: The main purpose of this study was to examine the relationship between flow experience and goal orientation theory, as well as, the differences in flow experience based on the orthogonal model of goal orientation theory. Two hundred and seventy eight athletes completed the Task and Ego Orientation Sport Questionnaire based on how they usually feel. The challenge and skills ratings were completed 1 h before the competition, based on how they felt at the exact time of answering. In the following, the Flow State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 52 publications
1
30
0
2
Order By: Relevance
“…For example, effective preparation is simply associated with flow occurrence, but not necessarily involved as a causal mechanism, as flow may still occur in its absence (Swann et al, 2012). In addition to qualitative work, extensive research on flow using questionnaire-based, correlational designs has further highlighted associations with flow (e.g., goal orientations -Stavrou et al, 2015). Thus, research on flow occurrence to date is primarily based on evidence of constructs associated with flow, rather than causal mechanisms, resulting in recent calls for the need to build towards a causal explanation of flow (Kimiecik & Stein, 1992;Swann, Crust, & Vella, 2017).…”
Section: How and When Does Flow Occur?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, effective preparation is simply associated with flow occurrence, but not necessarily involved as a causal mechanism, as flow may still occur in its absence (Swann et al, 2012). In addition to qualitative work, extensive research on flow using questionnaire-based, correlational designs has further highlighted associations with flow (e.g., goal orientations -Stavrou et al, 2015). Thus, research on flow occurrence to date is primarily based on evidence of constructs associated with flow, rather than causal mechanisms, resulting in recent calls for the need to build towards a causal explanation of flow (Kimiecik & Stein, 1992;Swann, Crust, & Vella, 2017).…”
Section: How and When Does Flow Occur?mentioning
confidence: 99%
“…For example, Csikszentmihalyi (1975) originally described flow as a "theoretical model of enjoyment" (pp.35-54), and discussed the "model of flow" (p.49), while later referring to "flow theory" (e.g., Nakamura & Csikszentmihalyi, 2009). In sport and exercise, researchers refer to the "flow model" (e.g., Koehn et al, 2013) and "flow theory" (e.g., Stavrou et al, 2015). Generally, challenge-skill balance has been considered the primary condition for flow occurrence (see Fong, Zaleski & Leach, 2015), and a number of models based on challenge-skill balance have emerged and evolved since Csikszentmihalyi"s (1975) initial work.…”
Section: Is the Conceptualization Of Flow A Theory?mentioning
confidence: 99%
“…Specifically, self-referenced appraisals of competence and success (e.g., personal improvement) represent task orientation, while defining success in normative terms (e.g., winning) symbolises ego orientation. Goal orientations are considered to be orthogonal rather than bipolar and an examination of their relationship to state flow found that high taskhigh ego and high tasklow ego athletes experienced significantly higher flow characteristics than low tasklow ego and low taskhigh ego athletes (Stavrou, Psychountaki, Georgiadis, Karteroliotis, & Zervas, 2015).…”
Section: Goal Orientationmentioning
confidence: 99%
“…En estas circunstancias, tiene lugar la aparición de conductas de logro negativas tales como un nivel de ejecución inferior al esperado, una disminución en el esfuerzo invertido o una falta de persistencia ante la presencia de obstáculos y dificultades (Duda & Nicholls, 1992;Stavrou, Psychountaky, Georgiadis, Karteroliotis, & Zervas, 2015). No obstante, Wang et al (2002) plantearon la posibilidad de que la orientación hacia el ego, pero no la orientación hacia la meta, interactuase con la percepción de competencia de un individuo.…”
unclassified